Machine learning for differentiating multiple diseases - CHEN JIALIANG; LIU QIN; SU QI; HUANG XIUJUAN (2025)
The present disclosure provides a personalized predictive risk assessment tool for determining the risk of a variety of diseases in a subject using microbiome. At present, only one disease or health condition can be detected by a risk prediction test using microbiome once. By simultaneously determining multiple diseases, the disclosed techniques may provide a cost-effective approach to support clinical decision making and thus help improve disease prevention and management. 本公开内容提供了使用微生物组确定对象中多种疾病风险的个人化预测风险评估工具。当前使用微生物组的风险预测测试一次只能检测一种疾病或健康状况。通过同时确定多种疾病，所公开的技术可以提供有成本效益的方法来支持临床决策制定，并因此帮助改善疾病预防和管理。